The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1016/j.eclinm.2021.101085
|View full text |Cite
|
Sign up to set email alerts
|

Maintaining safe lung cancer surgery during the COVID-19 pandemic in a global city

Abstract: Background: SARS-CoV-2 has challenged health service provision worldwide. This work evaluates safe surgical pathways and standard operating procedures implemented in the high volume, global city of London during the first wave of SARS-CoV-2 infection. We also assess the safety of minimally invasive surgery(MIS) for anatomical lung resection. Methods: This multicentre cohort study was conducted across all London thoracic surgical units, covering a catchment area of approximately 14.8 Million. A Pan-London Colla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 19 publications
(18 reference statements)
2
15
0
Order By: Relevance
“…A meta-analysis including 52 studies revealed similar findings in developed countries [11]. Our findings are also similar to findings from Saudi Arabia [(6 days) [9], (7 days) [8]], London (6 days) [23], the United States (6 days) [10], France (9 days) [12], and Tunisia (8 days) [13]. However, the median length of hospital stay in our study is higher than that reported in Australia (3 days) [19].…”
Section: Discussionsupporting
confidence: 90%
“…A meta-analysis including 52 studies revealed similar findings in developed countries [11]. Our findings are also similar to findings from Saudi Arabia [(6 days) [9], (7 days) [8]], London (6 days) [23], the United States (6 days) [10], France (9 days) [12], and Tunisia (8 days) [13]. However, the median length of hospital stay in our study is higher than that reported in Australia (3 days) [19].…”
Section: Discussionsupporting
confidence: 90%
“…COVID-19 infection during the perioperative period is well known to be a risk factor for increased length of stay, morbidity, and mortality. 8 SARS-CoV-2 infection shows a highly variable clinical course. The majority of infected people survive the disease asymptomatically or with mild symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Data came to show that the risk of COVID-19-related elective surgical mortality at the beginning of the pandemic was as high as 20-50% (10), and, as Dolan et al correctly point out, lung cancer patients were at a particularly high risk of COVID-19-related morbidity and mortality, both because of pre-existing comorbidity but also because of the direct effects of surgery on the lung and the immune system (1,6). The rates of postoperative COVID-19 infection following elective lung resection ranged from 0% (1,7), to as high as 28.5% (8), while the mortality rate in these patients was upwards of 40% (3,(6)(7)(8)(10)(11)(12).…”
Section: A Surgical Moratoriummentioning
confidence: 99%
“…In fact, many centers were able to maintain or resume a minimum volume of lung cancer surgery, and very importantly, to do so safely. Although the mortality in postoperative COVID-19 cases was high (up to around 40-50% (7,10)), the incidence was kept low, often less than 5% (1,7,8,10). Remarkably, most reported post-operative COVID-19 infections seem to have occurred during the first weeks of the pandemic; postoperative COVID-19 infections became much more rare during subsequent pandemic peaks (3) in spite of surgical volumes returning to prepandemic levels within several months, where they remained even during subsequent waves (6).…”
Section: Adapting and Implementing Solutionsmentioning
confidence: 99%